A Tri-Functionalized Oral Core-Melt Tablet (OCMT) for enhanced delivery of gastro-sensitive proteins and synthetic peptides - Choonara, Bibi Fatima (My University, 2017)
The global pharmaceutical biotechnology industry is continually growing and increased amounts of protein and peptide-based therapeutics are entering into the market. Conventionally, these therapeutic proteins and peptides are administered intravenously, subcutaneously or intramuscularly as oral routes of administration may result in their degradation in the gastrointestinal tract (O’ Connor, 2009). The parenteral route limits patient acceptability and convenience. Oral dosage forms, particularly tablets, are considered one of the most common and widely used routes of drug administration and accounts for approximately 50% of all dosage forms on the market (Oh et al., 2012). Thus, the development of oral technologies for therapeutic proteins and peptides remain a dynamic research field despite its many challenges. Successful oral delivery of proteins and peptides require the accomplishment of three key tasks: protection of the macromolecules from degradation in the gastrointestinal tract (GIT), permeation through the intestinal barrier and the absorption of molecules into the systemic circulation. Currently, no clinically useful oral formulations have been approved but several attempts have been made to overcome the challenges of low oral bioavailability resulting from poor absorption, poor permeation and enzymatic degradation of the proteins and peptides in the GIT. Present strategies attempt to provide structural protection of the proteins and peptides and improved absorption through the use of enzyme inhibitors, absorption enhancers, novel polymeric delivery systems and chemical modification. However, each of these technologies possesses limitations that preclude the successful oral delivery of proteins and peptides. The design and development of the novel Tri-functionalized OCMT attempts to breakthrough this market by triple targeting the major challenges governing successful oral delivery of proteins and peptides. Essentially, the Tri-functionalized OCMT is made up of three distinct functional components; the core-eutectic region, the outer polymer shell and the ‘smart’ polymeric sheet. Triple targeting was achieved by incorporating the bioactive into a core-melt archetype within the tablet and facilitating the process of in situ crosslinking which significantly affects the way the bioactive is protected within the compressed tablet matrix as well providing desirable bioactive release kinetics. In addition, the incorporation of a co-inhibitory ‘smart’ polymeric sheet provided added protection and enabled an improved absorption by virtue of its intrinsic properties and co-inhibition of the major determinants, CYP3A4 and Pgp, of poor absorption and low oral bioavailability. Lastly, targeting of enzymatic degradation was achieved by incorporation of a pH modifier that functions to transiently lower the micro-environmental pH and reduce the optimal environment for enzyme activity. The combination of the distinct formulatory components contained within the Tri-functionalized OCMT was extensively evaluated through in-depth in vitro physicochemical and physicomechanical characterization, ex vivo analyses and in vivo performance. In vitro and ex vivo characterization enabled the optimization of design variables and promoted the achievement of desirable functionalities for the attainment of optimum in vivo performance. In vivo analyses of the Tri-functionalized OCMT in the Large White pig model revealed an enhanced oral bioavailability of the incorporated peptides, octreotide and exenatide, following oral administration, as compared to their conventionally administered subcutaneous counterparts. In addition, pharmacokinetic analysis of the Tri-functionalized OCMT confirmed the maintenance of sustained, therapeutic levels of both octreotide and exenatide over the 24 hour period, supporting a convenient once-daily dosing. The rate at which protein and peptide-based therapeutics are developing is astounding, and this consequently increases the demand and focus towards achieving a simpler and more effective oral delivery of therapeutic proteins and peptides. The Tri-functionalized OCMT has successfully demonstrated its feasibility in enhancing the oral delivery of therapeutic proteins and peptides up to a preclinical stage. It may potentially serve as a viable alternative to the conventional parenteral route of administration for the treatment of various disease conditions by incorporating a multitude of proteins and peptides into its versatile design. The advancement of the Tri-functionalized OCMT to the clinical stage and beyond may ultimately improve patient outcomes and change the face of therapeutic protein and peptide delivery globally.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfillment of the requirements for the degree of Doctor of Philosophy. Department of Pharmacy and Pharmacology, University of the Witwatersrand, South Africa Johannesburg, 2017.